Levels of Activated FXII in Survivors of Myocardial Infarction – Association with Circulating Risk Factors and Extent of Coronary Artery Disease - Kohler, Hans P.; Carter, Angela M.; Stickland, Max H.; Grant, Peter J. (Thrombosis and Haemostasis, 1998)
Little data is available regarding the activated form of factor XIIa (FXIIa) in survivors of myocardial infarction. 292 Caucasian patients characterised for extent of coronary atheroma by angiography and for a past history of myocardial infarction and 77 healthy controls were included in the study. To investigate the relationship between coronary artery disease, activated factor XII and other circulating factors, we studied levels of FXIIa, cholesterol, triglycerides, fasting insulin, fibrinogen, FVII:C, t-PA antigen and PAI-1 antigen. Factor XIIa levels were higher in all patients [2.5 (2.3-2.6) ng/ml] and in patients with a history of MI [2.6 (2.4-2.9) ng/ml] than in controls [1.9 (1.7-2.1) ng/ml], p <0.0001. In patients, FXIIa levels positively correlated with FVII:C, BMI, cholesterol, insulin, PAI-1 antigen, t-PA antigen and triglycerides. In controls FXIIa levels only correlated with PAI-1 antigen and triglycerides. FXIIa levels were strongly associated with extent of coronary stenosis: 2.8 (2.6-3.1) ng/ml and 2.6 (2.3-2.9 ng/ml) in those with 2 and 3 vessels stenosed compared to 2.1 (1.9-2.3) ng/ml in those with 0 vessel stenosed (p = 0.0004). Activated FXII relates to both extent of coronary atheroma and to a past history of myocardial infarction and clusters with features of insulin resistance.